Enhanced out-of-plane electromechanical response of Janus ZrSeO. Issue 30 (27th July 2021) - Pham, Thi Hue; Ullah, Hamid; Shafique, Aamir; Kim, Hye Jung; Shin, Young-Han
Abstract : We investigate the compelling piezoelectric properties of Janus ZrSeO in monolayer and bulk structures using density functional theory calculations with a van der Waals correction. Abstract : Two-dimensional piezoelectric materials have attracted great attention as they could play a vital role in nano-electromagnetic systems. Herein, we investigate the compelling piezoelectric properties of Janus ZrSeO in monolayer and bulk structures using density functional theory calculations with a van der Waals correction. One of the two independent out-of-plane piezoelectric coefficients ( e 31 ) of the bulk ZrSeO is as high as 287.60 pC m −1, which is over five times larger than that of monolayer ZrSeO due to charge changes in the internal structure within each Zr, Se, and O layer. Interestingly, another large negative out-of-plane piezoelectric stress coefficient ( e 33 ) of bulk ZrSeO (−467.40 pC m −1 ) results from the displacement difference between the electronic and ionic center positions, which is at least three times larger than those previously reported for Janus Mo/W/Hf-based transition metal dichalcogenides. The charge transformation between atoms under strain induces negative piezoelectric stress, a process that is clarified using maximally localized Wannier functions (MLWF) and Bader charge analysis. This research also reveals the dependence of piezoelectricity in Janus MXY on the metal (M = Zr, Hf, W, Mo) and chalcogenide (X, Y = S, Se, O) components, which are directly proportional to the electronegativity and the atomic size difference.